How adversity quotient and interpersonal communication affects teacher organizational citizenship behavior? - Sulistiasih Sulistiasih; Widodo Widodo (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study explored the empirical effect of adversity quotient (AQ) and interpersonal communication on teachers’ organizational citizenship behavior (OCB) mediated by organizational commitment. A questionnaire in Likert scale model collected research data. The sample were 469 teachers of primary schools in Indonesia selected by accidental sampling. Data analysis used path analysis supported by descriptive statistics and correlational matric. The research result indicated that AQ and interpersonal communication significantly affect teachers’ OCB, directly and indirectly, mediated by organizational commitment. Thus, the teachers’ OCB can enhance through AQ, interpersonal communication, and organizational commitment. Besides, a new model regarding the effect of AQ and interpersonal communication on teachers’ OCB mediated by organizational commitment also was confirmed. Therefore, the researchers and practitioners can adopt a new empirical model to increase teachers’ OCB through AQ, interpersonal communication, and organizational commitment in the future.